Nuclear Magnetic Resonance Reveals Disordered Level-Crossing Physics in the Bose-Glass Regime of the Br-Doped Ni(Cl1−xBrx)2−4SC(NH2)2 Compound at a High Magnetic Field - Orlova, Anna; Blinder, Rémi; Kermarrec, Edwin; Dupont, Maxime; Laflorencie, Nicolas; Capponi, Sylvain; Mayaffre, Hadrien; Berthier, Claude; Paduan-Filho, Armando; Horvatić, Mladen (Physical review letters, 2017)
By measuring the nuclear magnetic resonance (NMR) 1/T_1 relaxation rate in the Br (bond) doped DTN compound, Ni(Cl(1-x)Br_x)2-4SC(NH2)2 (DTNX), we show that the low-energy spin dynamics of its high magnetic field "Bose-glass" regime is dominated by a strong peak of spin fluctuations found at the nearly doping-independent position H* = 13.6 T. From its temperature and field dependence we conclude that this corresponds to a level crossing of the energy levels related to the doping-induced impurity states. Observation of the local NMR signal from the spin adjacent to the doped Br allowed us to fully characterize this impurity state. We have thus quantified a microscopic theoretical model that paves the way to better understanding of the Bose-glass physics in DTNX, as revealed in the related theoretical study [M. Dupont, S. Capponi, and N. Laflorencie, Phys. Rev. Lett. 118, 067204 (2017), arXiv:1610.05136].